Key success factors for interstate roll-on roll-off short sea shipping in the Brunei, Indonesia, Malaysia and Philippines East ASEAN growth area / Aminuddin Md Arof - Md Arof, Aminuddin (Institute of Graduate Studies, UiTM, 2016)
The aim of this study is to determine the key success factors for interstate Ro-Ro Short Sea Shipping (SSS) operations in the Brunei, Indonesia, Malaysia and Philippines East ASEAN Growth Area (BIMP-EAGA). Although the literature has addressed a myriad of important factors through earlier research, the identification of the key determinants for the success of SSS operations in this sub-region is imperative because each route or corridor has its own peculiarities. Hence, this study is expected to assist SSS authorities, private investors and financial institutions to focus their limited resources on several key factors that could ensure the success of their SSS undertakings. The initial step in the research design involved the identification of relevant factors that have contributed towards successful SSS operations through a process of literature review. However, the breath of the literature on SSS outside Europe and North America, which may differ in the required variables for a successful SSS operation is still limited. Hence, a Delphi survey has been conducted with sub-regional SSS experts through a purposive sampling method to identify any new determinants and assess their opinions on the relative importance of all the determinants involved…